2016
DOI: 10.2175/106143015x14212658614478
|View full text |Cite
|
Sign up to set email alerts
|

Removing Grit During Wastewater Treatment:CFD Analysis of HDVS Performance

Abstract: Computational Fluid Dynamics (CFD) was used to simulate the grit and sand separation effectiveness of a typical hydrodynamic vortex separator (HDVS) system. The analysis examined the influences on the separator efficiency of: flow rate, fluid viscosities, total suspended solids (TSS), and particle size and distribution. It was found that separator efficiency for a wide range of these independent variables could be consolidated into a few curves based on the particle fall velocity to separator inflow velocity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The Overflow Rate (OFR) of a settler has the dimensions of velocity and can be used to analyze the particle size that will be removed in the tank by equating it to the particle's settling velocity using Newton's Law, thus providing the basis for the design of grit separators [8,9]. In this study, the overflow rates were 0.078 m/s for the MTS and 0.366 m/s for the FVS, which translate to the settling velocities of particles with a SES of 95 and 206 μm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The Overflow Rate (OFR) of a settler has the dimensions of velocity and can be used to analyze the particle size that will be removed in the tank by equating it to the particle's settling velocity using Newton's Law, thus providing the basis for the design of grit separators [8,9]. In this study, the overflow rates were 0.078 m/s for the MTS and 0.366 m/s for the FVS, which translate to the settling velocities of particles with a SES of 95 and 206 μm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CFD models (openFOAM, Ansys, COMSOL) enables prediction of flow fields and turbulent mixing to the various levels of detail. A large number of studies have shown that CFD is a powerful tool for analysing and optimising particular water treatment processes, such as optimization of ozone contactors for microbial inactivation [60], [61], disinfection performance of UV reactors [62], oxidation processes [63], investigation of electrochemical variables in the operation of a continuous upflow electrocoagulation process in treating textile wastewater [64], simulation of the grit and sand separation effectiveness of a typical hydrodynamic vortex separator (HDVS) system [65], simulation of mixing characteristics of a small circular anaerobic digester tank [66], working performance of closed-loop bioreactor [67][66], verification of compliance of a water reclamation plant disinfection stage with respect to modal time [68], or analysing efficiency of the electrocoagulation (EC) process with stainless-steel electrodes for total nitrogen removal [69].…”
Section: Numerical Modellingmentioning
confidence: 99%